2021
DOI: 10.3390/membranes11050300
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration Composite Membranes Based on KIT-6 and Functionalized KIT-6 Nanoparticles in a Polymeric Matrix with Enhanced Performances

Abstract: The nanofiltration composite membranes were obtained by incorporation of KIT-6 ordered mesoporous silica, before and after its functionalization with amine groups, into polyphenylene-ether-ether-sulfone (PPEES) matrix. The incorporation of silica nanoparticles into PPEES polymer matrix was evidenced by FTIR and UV–VIS spectroscopy. SEM images of the membranes cross-section and their surface topology, evidenced by AFM, showed a low effect of KIT-6 silica nanoparticles loading and functionalization. The performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…In recent years, poly(1,4-phenylene ether ether sulfone) (PPEES) was studied for its practical application as a separation membrane, mainly due to its high thermal resistance, film-forming capacity, good chemical stability, good solubility, and easy preparation with low-cost [ 14 , 15 ]. Our previous research revealed that PPEES could be used to prepare ultra- and nano-filtration membranes for polyphenolic compound concentration from natural extracts [ 5 , 16 ]. However, due to its hydrophobic nature, PPEES is easily fouled, resulting in a gradual decrease in permeate flux.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, poly(1,4-phenylene ether ether sulfone) (PPEES) was studied for its practical application as a separation membrane, mainly due to its high thermal resistance, film-forming capacity, good chemical stability, good solubility, and easy preparation with low-cost [ 14 , 15 ]. Our previous research revealed that PPEES could be used to prepare ultra- and nano-filtration membranes for polyphenolic compound concentration from natural extracts [ 5 , 16 ]. However, due to its hydrophobic nature, PPEES is easily fouled, resulting in a gradual decrease in permeate flux.…”
Section: Introductionmentioning
confidence: 99%